Evaluation of scorpion sting incidence in turkey - Ozkan,O. (2008)
Scorpion stings are common in Turkey due to its geographical location, climate and socioeconomic structure. Scorpion envenomation cases are a considerable public health problem in all regions of the country. Important health-threatening scorpions in Turkey are Androctonus crassicauda, Leiurus quinquestriatus, Mesobuthus gibbosus and M. eupeus, all of which belong to the Buthidae family. They are described to be potentially dangerous to humans. So far, there is no study about scorpion sting incidence covering all geographical regions of Turkey; therefore, in this study, we analyzed the frequency of scorpion sting cases in the country. A total of 24,261 scorpion sting cases were reported during 2005. Most of which (about 80%) occurred in the Southeastern Anatolia (30.4%), Mediterranean Sea (24.9%) and Aegean regions (23.5%), where medically important scorpion species are found. The sting cases mostly occurred during the summer period. Our results suggest that scorpion stings are an important problem in Turkey. This simple descriptive study will help develop interventions to prevent scorpion stings, which should take local sting cases into consideration.